Peran Jurnalistik Dakwah dalam Mengimplemnetasikan Pesan Dakwah dengan Baik - Efendi, Erwan; Syarbaini; Salshabila, Jihan; Maulana, Gilang; Dalimunthe, Yaqub (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to allay concerns regarding "the role of da'wah journalism in implementing good da'wah messages" included in the media management curriculum. The aim of this research is to understand, identify, and provide insight into how a journalist can effectively adopt ethical discourse. to provide a clear example of how a journalist should apply sound preaching advice based on research findings. a journalist can be effective using the following criteria: must come from Allah SWT, must uphold all human rights there must be balance in every action, and there must be a balance between ideals and reality. Therefore, there are several things that need to be understood and noticed. In particular, writing with a preaching nuance will be consumed by the media, which will determine whether it is a specifically Islamic article or not.